Characterisation and therapeutic manipulation of the gut microbiome in inflammatory bowel disease. Issue 3 (March 2016) - Schulberg, J.; De Cruz, P.
Abstract : Inflammatory bowel diseases are thought to develop as a result of dysregulation of the relationship that exists between the gut microbiota, host genetics and the immune system. The advent of culture‐independent techniques has revolutionised the ability to characterise the role of the gut microbiota in health and disease based on the microbiota's genetic make‐up. Inflammatory bowel diseases are characterised by dysbiosis which is an imbalance between pro‐ and anti‐inflammatory bacteria and a reduction in bacterial diversity. Emerging data suggest that it is not only the presence of the gut microbiota but the functional activity of the microbiota that appears to play an important role in health and disease. Current strategies to manipulate therapeutically the gut microbiota using dietary modification, prebiotics, probiotics, antibiotics and faecal microbiota transplantation aim to restore the balance to a state of normobiosis. However, the ability of such strategies to correct dysbiosis and thereby achieve therapeutic benefit is yet to be fully characterised.